1986
DOI: 10.1177/0022427886023002004
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Labeling Theory Using Longitudinal Data

Abstract: This article uses panel data and multiple regression of follow-up on baseline variables to test direction of causality among drug use behavior, informal labels, and formal labels. Baseline and follow-up data were collected on a random sample of 100 adolescents (54 males) and a clinical sample of 88 adolescents (49 males). Separate regressions were performed on male and female respondents using both samples. Slope differences across samples were tested using interaction terms computed by multiplying sample type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…Although the ages of self identified criminality ranged widely from age 8 to the early 20 s, the women who saw themselves as criminal reportedly held that view on average when they were 16 or 17 years old. Drug use and sales were significantly related to women's later definition of themselves as a criminal, a finding which was supported by Ray and Downs (1986) who concluded that young females construct their self-label in response or following drug use behavior. It is also possible that as drug use and behaviors have become more criminalized with stiffer penalties, more young women have been brought into the system (Buchanan and Young 2000).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although the ages of self identified criminality ranged widely from age 8 to the early 20 s, the women who saw themselves as criminal reportedly held that view on average when they were 16 or 17 years old. Drug use and sales were significantly related to women's later definition of themselves as a criminal, a finding which was supported by Ray and Downs (1986) who concluded that young females construct their self-label in response or following drug use behavior. It is also possible that as drug use and behaviors have become more criminalized with stiffer penalties, more young women have been brought into the system (Buchanan and Young 2000).…”
Section: Discussionmentioning
confidence: 78%
“…Three examples are before the felony conviction process to better understand the process of how individuals come to identify with being a criminal, which may include factors such as parental neglect, sexual abuse, or substance abuse that may prevent the development of high self esteem (Crocker and Major 1989). Another point in time might be immediately after justice intervention to see how social sanctions might influence future deviant behavior, such as approaches used by Ray and Downs (1986), Kaplan and Damphousse (1997) or by Bernburg et al (2006). A third related avenue is how stigmatizing labels are resisted depending on the proportion of positive social associations, or on the individual's level of confidence about the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding juveniles, Ageton and Elliott (1974) hypothesized that "males are more likely to be affected negatively by police contact than females," but no rationale was associated with that expectation. Somewhat later, Ray and Downs (1986), also in the context of adolescents, articulated the opposite expectation. On the premise that "females are expected to be more attentive to interpersonal relationships than men," they hypothesized that "labels may exert more of an influence on behavior for females than males " (1986: 171).…”
Section: Labeling Effects: Conceptual Issuesmentioning
confidence: 99%
“…For example, longitudinal studies show that no causal relationship exists between formal labeling and the adoption of a "drug-user" label among drugusing adolescents (Ray & Downs, 1986). Additionally, Ray and Downs found that, contrary to the predictions of labeling theory, formal labeling had no causal effect on the substance use behaviors of drug-using adolescent females.…”
Section: Perceived Delinquent Label and Behaviormentioning
confidence: 94%